A Systematic Review and Meta-Analysis of Machine Perfusion vs. Static Cold Storage of Liver Allografts on Liver Transplantation Outcomes: The Future Direction of Graft Preservation - Jia, Junjun; Nie, Yu; Li, Jianhui; Xie, Haiyang; Zhou, Lin; Yu, Jun; Zheng, Shu-Sen (Frontiers in Medicine, 2020)
Background: Machine perfusion (MP) and static cold storage (CS) are two prevalent methods for liver allograft preservation. However, the preferred method remains controversial. Aim: To conduct a meta-analysis on the impact of MP preservation on liver transplant outcome. Methods: PubMed, EMBASE, and Cochrane Library databases were systematically searched to identify relevant trials comparing the efficacy of MP vs. CS. Odds ratios (OR) and fixed-effects models were calculated to compare the pooled data. Results: Ten prospective cohort studies and two randomized controlled trials (RCTs) were included (MP livers vs. CS livers = 315:489). Machine perfusion demonstrated superior outcomes in posttransplantation aspartate aminotransferase levels compared to CS (P < 0.05). The overall incidence of early allograft dysfunction (EAD) was significantly reduced with MP preservation than CS [OR = 0.46; 95% confidence interval (CI) = 0.31–0.67; P < 0.0001]. The incidence of total biliary complications (OR = 0.53; 95% CI = 0.34–0.83; P = 0.006) and that of ischemic cholangiopathy (OR = 0.39; 95% CI = 0.18–0.85; P = 0.02) were significantly lower in recipients with MP preservation compared with CS preservation. Hypothermic machine perfusion (HMP) but not normothermic machine perfusion (NMP) was found to significantly protect grafts from total biliary complications and ischemic cholangiopathy (P < 0.05). However, no significant differences could be detected utilizing either HMP or NMP in primary nonfunction, hepatic artery thrombosis, postreperfusion syndrome, 1-year patient survival, or 1-year graft survival (P > 0.05). Conclusions: Machine perfusion is superior to CS on improving short-term outcomes for human liver transplantation, with a less clear effect in the longer term. Hypothermic machine perfusion but not NMP conducted significantly protective effects on EAD and biliary complications. Further RCTs are warranted to confirm MP's superiority and applications.